2022
DOI: 10.3390/vaccines10040583
|View full text |Cite
|
Sign up to set email alerts
|

Local Response and Barrier Recovery in Elderly Skin Following the Application of High-Density Microarray Patches

Abstract: The high-density microneedle array patch (HD-MAP) is a promising alternative vaccine delivery system device with broad application in disease, including SARS-CoV-2. Skin reactivity to HD-MAP applications has been extensively studied in young individuals, but not in the >65 years population, a risk group often requiring higher dose vaccines to produce protective immune responses. The primary aims of the present study were to characterise local inflammatory responses and barrier recovery to HD-MAPs in elderly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Pigmentation was noted in three clinical studies,7 14 16 which lasted a maximum of 189 days in JEV MAPs 7. Two studies reported wet bleeding, typically resolving quickly within 30 min 39 40. Oedema was reported in two studies and resolved by day 8 40 41.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…Pigmentation was noted in three clinical studies,7 14 16 which lasted a maximum of 189 days in JEV MAPs 7. Two studies reported wet bleeding, typically resolving quickly within 30 min 39 40. Oedema was reported in two studies and resolved by day 8 40 41.…”
Section: Resultsmentioning
confidence: 97%
“…One RCT was only partly blinded when comparing MAP to N&S, but did not blind active and placebo MAPs 12. Loss to follow-up in four longitudinal studies was not reported or could not be determined 15 38–40…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations